Reversing the great degradation of nature by reducing factors related to cropland expansion - Stephen Polasky; Erik Nelson; David Tilman; James Gerber; Justin Andrew Johnson; Erwin Corong; Forest Isbell; Jason Hill; Craig Packer (Proceedings of the National Academy of Sciences, 2026)
As one of the main causes of habitat loss, agricultural cropland expansion is a major threat to biodiversity. We analyze past and anticipated future trends in population, per capita crop demand, and crop yield to estimate agricultural cropland requirements globally by 2050 and 2100, assuming moderate levels of climate change. According to a model of “business as usual,” higher-income countries would be expected to show little or no net growth in cropland by the end of the century whereas cropland area could nearly double in lower-income countries. We consider two strategies to reduce global cropland expansion: decreasing per capita crop demand in higher-income countries by eating healthier diets, reducing food waste, and reducing biofuel production, and accelerating economic development in lower-income countries. Economic development in lower-income countries could reduce future cropland requirements via slower population growth, improved crop yield, and higher volumes of global crop trade, which could more than offset rising per capita crop demand. These impacts would far exceed reductions in cropland requirements from decreased crop demand in higher-income countries. Further, by combining accelerated economic development in lower-income countries with reduced crop demand in higher-income countries in tandem with reduced trade friction, global cropland requirements could shrink dramatically by the year 2100. Although economic growth is often considered to work in opposition to environmental conservation, accelerating economic development in lower-income countries would not only help alleviate poverty but could also confer benefits for biodiversity and global climate change.